MASTERMIND: Bringing Microbial Diagnostics to the Clinic. (24th December 2016) - Patel, Robin; Tsalik, Ephraim L.; Petzold, Elizabeth; Fowler, Vance G.; Klausner, Jeffrey D.; Evans, Scott; ,
Summary: New diagnostics are needed to facilitate appropriate use of antimicrobial agents. The Master Protocol for Evaluating Multiple Infection Diagnostics (MASTERMIND) concept for advancement of infectious diseases diagnostics is described, wherein a single subject's sample(s) evaluates multiple diagnostic tests. Abstract: New diagnostics are urgently needed to address emerging antimicrobial resistance. The Antibacterial Resistance Leadership Group proposes a strategy called MASTERMIND (Master Protocol for Evaluating Multiple Infection Diagnostics) for advancement of infectious diseases diagnostics. The goal of this strategy is to generate the data necessary to support US Food and Drug Administration clearance of new diagnostic tests by promoting research that might not have otherwise been feasible with conventional trial designs. MASTERMIND uses a single subject's sample(s) to evaluate multiple diagnostic tests at the same time, providing efficiencies of specimen collection and characterization. MASTERMIND also offers central trial organization, standardization of methods and definitions, and common comparators.